Kelimpahan Spesies Lalat Buah (Diptera: Tephritidae) dan Parasitoidnya yang Berasosiasi pada Tanaman Belimbing (Averrhoa carambola L.) di Kabupaten Gianyar - PUTRA, I NYOMAN WIDNYANA; SUSILA, I WAYAN; BAGUS, I GUSTI NGURAH (Agrotrop : Journal on Agriculture Science; Vol 9 No 1 (2019), 2019)
Abundance of Fruit Fly Species (Diptera: Tephritidae) and Its Parasitoid Associated on Star Fruit Plants (Averrhoa carambola L.) in Gianyar regency. This study was conducted to determine the abundance of fruit flies, and itsspecies of parasitoid on starfruit plants in Gianyar regency. Samples of star fruit attacked by fruit fly was taken purposively. The purpose of this study was to know the abundance, composition, and percentage of damage, kinds of parasitoid and parasitization rate. The results showed that was found 2 kinds of fruit flies, that are Bactrocera. carambolae and B. papayae . B. carambolae was dominant in all districts in Gianyar Regency compare them B. papaya e . In Sukawati district was 64%, (492 adults), Blahbatuh district was 59.817% (460 adults), Ubud district was 61.528% (491 adults), Payangan district was 55.476% (390 adults), Tampaksiring district was 55.001% (390 adults), respectively. Meanwhile , B. papayae in Sukawati district was 35.348%, (269 adults), Blahbatuh district was 40.182% (309 adults), Ubud district was 38.471% (307 adults), Payangan district was 44.523% (313 adults) and Tampaksiring district was 40.998% (271 adults), respectively. The average of damage percentage was 86.33%. There are 3 kinds of parasitoids associated on fruit flies in starfruit plants in Gianyar regency. The parasitoid are Diachasmimorpha sp , Opius sp. and Fopius arisanus . The average parasitization rate was 11.12%, with the highest parasitization rate in Ubud district was 12.40% and the lowest in Tampaksiring districtwas 9.58%.